Cardiac cine magnetic resonance fingerprinting for combined ejection fraction, T1 and T2 quantification. (5th June 2020) - Hamilton, Jesse I.; Jiang, Yun; Eck, Brendan; Griswold, Mark; Seiberlich, Nicole
Abstract : This study introduces a technique called cine magnetic resonance fingerprinting (cine‐MRF) for simultaneous T1, T2 and ejection fraction (EF) quantification. Data acquired with a free‐running MRF sequence are retrospectively sorted into different cardiac phases using an external electrocardiogram (ECG) signal. A low‐rank reconstruction with a finite difference sparsity constraint along the cardiac motion dimension yields images resolved by cardiac phase. To improve SNR and precision in the parameter maps, these images are nonrigidly registered to the same phase and matched to a dictionary to generate T1 and T2 maps. Cine images for computing left ventricular volumes and EF are also derived from the same data. Cine‐MRF was tested in simulations using a numerical relaxation phantom. Phantom and in vivo scans of 19 subjects were performed at 3 T during a 10.9 seconds breath‐hold with an in‐plane resolution of 1.6 x 1.6 mm 2 and 24 cardiac phases. Left ventricular EF values obtained with cine‐MRF agreed with the conventional cine images (mean bias −1.0%). Average myocardial T1 times in diastole/systole were 1398/1391 ms with cine‐MRF, 1394/1378 ms with ECG‐triggered cardiac MRF (cMRF) and 1234/1212 ms with MOLLI; and T2 values were 30.7/30.3 ms with cine‐MRF, 32.6/32.9 ms with ECG‐triggered cMRF and 37.6/41.0 ms with T2 ‐prepared FLASH. Cine‐MRF and ECG‐triggered cMRF relaxation times were in good agreement. Cine‐MRF T1 values were significantly longer than MOLLI, and cine‐MRF T2 values were significantly shorter than T2 ‐prepared FLASH. In summary, cine‐MRF can potentially streamline cardiac MRI exams by combining left ventricle functional assessment and T1 ‐T2 mapping into one time‐efficient acquisition. Abstract : This study introduces a dictionary‐based technique, called cine magnetic resonance fingerprinting (cine‐MRF), for jointly acquiring T1 and T2 maps and cine images for ejection fraction quantification in one breath‐hold. Data are collected using a free‐running FISP‐based MRF sequence, and nonrigid registration is used to improve precision and SNR. Cine‐MRF can potentially streamline cardiac MRI exams by combining T1 ‐T2 mapping and functional assessment into one time‐efficient scan.